2012
DOI: 10.1016/j.polymdegradstab.2011.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale analysis of water uptake and erosion in biodegradable polyarylates

Abstract: The role of hydration in degradation and erosion of materials, especially biomaterials used in scaffolds and implants, was investigated by studying the distribution of water at length scales from 0.1 nm to 0.1 mm using Raman spectroscopy, small-angle neutron scattering (SANS), Raman confocal imaging, and scanning electron microscopy (SEM). The measurements were demonstrated using L-tyrosine derived polyarylates. Bound- and free- water were characterized using their respective signatures in the Raman spectra. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Following incubation, the samples were removed from water, wiped free of surface moisture and weighed. WU was calculated using the following formula: normalWnormalU |%= 100%×MnormalfM0M0 where M 0 represents the original dry weight of the sample and M f —the weight of the sample after being kept in water. Five replicates were performed for each of the mesh samples.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following incubation, the samples were removed from water, wiped free of surface moisture and weighed. WU was calculated using the following formula: normalWnormalU |%= 100%×MnormalfM0M0 where M 0 represents the original dry weight of the sample and M f —the weight of the sample after being kept in water. Five replicates were performed for each of the mesh samples.…”
Section: Methodsmentioning
confidence: 99%
“…Following incubation, the samples were removed from water, wiped free of surface moisture and weighed. WU was calculated using the following formula 23 :…”
Section: Characterization Of the Meshesmentioning
confidence: 99%
“…Water uptake was obtained for the selected polymers from the L-tyrosine-derived polyarylates combinatorial library ( Table 1 ) using 3 H-labeled water, as described previously [ 45 ]. Briefly, films 1 cm in diameter were incubated in 3 H-radiolabeled water (0.2 μ Ci/mL) at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…22 Studies of dental materials showed chemical differences in ceramic properties, 23 and the role of hydration was studied in the degradation of other implants and scaffold materials. 24 The progress described above was accomplished through development of better and more efficient instrumentation, such as those noted in a recent review. 25 Recent advances in instrumentation suggest continued growth in the use of Raman microscopy.…”
Section: ■ Spontaneous Raman Microscopymentioning
confidence: 99%
“…Raman microscopy was able to discriminate between cholesterol esters, cholesterol, and triglycerides in atherosclerotic plaques in rabbits . Studies of dental materials showed chemical differences in ceramic properties, and the role of hydration was studied in the degradation of other implants and scaffold materials …”
Section: Spontaneous Raman Microscopymentioning
confidence: 99%